Tinjauan Pemenuhan Dokumentasi ISO 9001:2015 PT. Teno Indonesia - Dave Warren Tandiono; Jani Rahardjo (Jurnal Titra, 2017)
PT. Teno Indonesia is a company engaged in the field of services that is pile building pole. This research objective is to assist the company in preparing the upgrading of quality management system from ISO 9001: 2008 to ISO 9001: 2015. Requirements to be added during preparation are analysis of external internal issues and interested parties (clauses 4.1 & 4.2) and risk analysis (clause 6.1). Analysis of external internal issues is carried out on all departments with SWOT analysis methods (Strength, Weakness, Opportunities, Threat). Risk analysis is performed on all ISO 9001: 2008 document procedures in which are then grouped into each department using FMEA (Failure Modes and Effect Analysis) method. PT. Teno Indonesia already has considerable control over external internal issues and potential failures. There is also a possibility that there are still several processes from each department that have high risks and need to be reduced. Implementation of risk analysis and preventive action and results have been implemented on Amega Crown Project for one week. The preliminary quality review shows a level of compliance with the requirements of ISO 9001:2015 is 92%, but the final review is not measureable yet because it is only document fullfilment and has not been implemented.